Nuclear Galectin-1 promotes KRAS -dependent activation of pancreatic cancer stellate cells - Judith Vinaixa; Neus Martínez-Bosch; Joan Gibert; Noemí Manero-Rupérez; Patricia Santofimia-Castaño; Federico G. Baudou; Renzo E. Vera; David R. Pease; Mar Iglesias; Sandhya Sen; Xiyin Wang; Luciana L. Almada; et al. (Proceedings of the National Academy of Sciences, 2025)
Pancreatic ductal adenocarcinoma (PDAC) is one of the most aggressive cancers, primarily due to its complex tumor microenvironment (TME), which drives both disease progression and therapy resistance. Understanding the molecular mechanisms governing TME dynamics is essential for developing new treatment strategies for this devastating disease. In this study, we uncover an oncogenic role for Galectin-1 (Gal1), a glycan-binding protein abundantly expressed by activated pancreatic stellate cells (PSCs), a key component of the PDAC TME that orchestrates tumor progression. Our findings reveal that Gal1 expression is elevated in the nucleus of human PSCs in both tissue samples and cultured cell lines. Using chromatin immunoprecipitation followed by sequencing analysis (ChIP-seq), we identify Gal1 occupancy at the promoters of several cancer-associated genes, including KRAS , a pivotal oncogene involved in PDAC pathogenesis. We demonstrate that Gal1 binds to the KRAS promoter, sustaining KRAS expression in PSCs, which, in turn, maintains PSC activation and promotes the secretion of protumorigenic cytokines. Mechanistically, Gal1 is required to preserve histone H3 lysine 4 monomethylation levels and to recruit the histone methyltransferase MLL1 to target promoters. Collectively, our findings define a nuclear function of Gal1 in modulating the transcriptional landscape of cancer-associated genes in PSCs within the PDAC TME, mediated through an epigenetic mechanism. These insights enhance our understanding of PDAC pathology and open potential avenues for therapeutic interventions targeting intracellular Gal1.